Genome-Wide SNP Discovery in Indigenous Cattle Breeds of South Africa - Zwane, Avhashoni A.; Schnabel, Robert D.; Hoff, Jesse; Choudhury, Ananyo; Makgahlela, Mahlako Linah; Maiwashe, Azwihangwisi; Van Marle-Koster, Este; Taylor, Jeremy F. (Frontiers in Genetics, 2019)
Single nucleotide polymorphism arrays have created new possibilities for performing genome-wide studies to detect genomic regions harboring sequence variants that affect complex traits. However, the majority of validated SNPs for which allele frequencies have been estimated are limited primarily to European breeds. The objective of this study to perform SNP discovery in three South African indigenous breeds (Afrikaner, Drakensberger and Nguni) using whole genome sequencing. DNA was extracted from blood and hair samples, quantified and prepared at 50ng/µl concentration for sequencing at the Agricultural Research Council Biotechnology Platform using an Illumina HiSeq 2500. The fastq files were used to call the variants using the Genome Analysis Tool Kit. A total of 1,678,360 were identified as novel using Run 6 of 1000 Bull Genomes Project. Annotation of the identified variants classified them into functional categories. Within the coding regions, about 30% of the SNPs were nonsynonymous substitutions that encode for alternate amino acids. The study of distribution of SNP across the genome identified regions showing notable differences in the densities of SNPs among the breeds and highlighted many regions of functional significance. Gene ontology terms identified genes such as MLANA, SYT10 and CDC42EP5 that have been associated with coat colour in mouse, and ADAMS3, DNAJC3 and PAG5 genes have been associated with fertility in cattle. Further analysis of the variants detected 688 candidate selective sweeps (ZHp Z-scores ≤ -4) across all three breeds, of which 223 regions were assigned as being putative selective sweeps (ZHp scores ≤ -5). We also identified 96 regions with extremely low ZHp Z-scores (≤ -6) in Afrikaner and Nguni. Genes such as KIT and MITF that have been associated with skin pigmentation in cattle and CACNA1C, which has been associated with biopolar disorder in human, were identified in these regions. This study provides the first analysis of sequence data to discover SNPs in indigenous South African cattle breeds. The information will play an important role in our efforts to understand the genetic history of our cattle and in designing appropriate breed improvement programmes.